Pathophysiological mechanisms determining sex differences in circulating levels of cardiac natriuretic peptides and cardiac troponins - Clerico, Aldo; Masotti, Silvia; Musetti, Veronica; Passino, Claudio (Journal of Laboratory and Precision Medicine; Vol 4 (February 2019): Journal of Laboratory and Precision Medicine, 2019)
It is well known that adult fertile women have about two-fold higher circulating levels of cardiac natriuretic peptides (NPs) than men of the same age. Conversely, men have on average higher circulating levels of cardiac troponin I (cTnI) and T (cTnT) than women. Furthermore, the circulating levels of both cardiac NPs and troponins progressively increase after 65 years of age in both sexes. From a physiological point of view, these differences in circulating levels between cardiac NPs and troponins are closely related to production, secretion and peripheral degradation of these biomarkers; these complex physiological mechanisms are differently regulated in men and women. Some cardiac and extra-cardiac diseases with sex-related prevalence can also affect these physiological mechanisms, and in this way to allow more difficult the clinical interpretations of cardiac biomarker measurement with immunoassay methods. The aim of this review article is to discuss the available evidence of the possible different mechanisms related to production, secretion and degradation of cardiac NPs and cardiac troponins in men and women.